Canine and Feline Oral Cavity Tumours and Tumour-like Lesions: a Retrospective Study of 486 Cases (2015–2017). (October 2019) - Mikiewicz, M.; Paździor-Czapula, K.; Gesek, M.; Lemishevskyi, V.; Otrocka-Domagała, I.
Summary: Oral cavity tumours and tumour-like lesions are common in dogs and cats, and their diagnosis and classification requires histopathological examination. The aim of this study was to analyse retrospectively oral cavity lesions in dogs and cats in order to evaluate the distribution of inflammatory, hyperplastic and neoplastic lesions manifested as tumours. A total of 486 oral cavity tumours and tumour-like lesions (340 canine; 146 feline), diagnosed routinely from 2015 to 2017, were included. The lesions were classified as inflammatory, hyperplastic or neoplastic (benign and malignant). Histopathological diagnosis was based on haematoxylin and eosin staining and, when necessary, May-Grünwald–Giemsa (for mast cell tumours) or Masson's Fontana (for melanomas) stains or immunohistochemistry (for CD3, CD79α and S100 markers). For dogs, 29.11% (99/340) of the lesions were benign tumours, 24.12% (82/340) were hyperplastic lesions and 14.7% (50/340) were inflammatory lesions. For cats, 4.79% (7/146) were benign tumours, 15.07% (22/146) were hyperplastic lesions and 57.53% (84/146) were inflammatory lesions. Furthermore, 23.24% (79/340) of canine cases were diagnosed with gingival hyperplasia and 19.12% (65/340) were diagnosed with peripheral odontogenic fibroma, while 43.84% (64/146) of feline cases were diagnosed with chronic lymphoplasmacytic stomatitis. Malignant tumours in dogs and cats constituted 32.06% (109/340) and 21.91% (32/146) of the lesions, respectively, with high-grade melanoma in dogs and squamous cell carcinoma in cats being the most common.